PEMIKIRAN POLITIK NICCOLO MACHIAVELLI: STUDI KASUS DINASTI UMAYYAH - fahrezy, Alfin falah; Hamid, Rizal Al (Living Islam: Journal of Islamic Discourses, 2021)
The Umayyad dynasty was an Islamic caliphate regime after the khulafa urrasydin which managed to maintain its power for 90 years before being overthrown by the Abbasids. This dynasty is famous for its political stability from the beginning of his reign to a systematized public administration and military. Nevertheless, this dynasty raised pros and cons in terms of morality which were considered to deviate from Islamic teachings at least during the political revolution and post-Caliph Mu'awiyah. The author tries to examine the practice of such government using the political theory of Niccolo Machiavelli in which there are also thoughts about the ethics of power. This study tries to answer several questions, namely what is the ideal government practice in the book "Il Principe" by Niccolo Machiavelli? and whether the practice of Umayyad dynasty government can be said to be ideal in terms of administration and ethics of power in Machiavelli's perspective? This research is a qualitative research with primary sources in the form of historical literature about the Umayyad Dynasty and the books by Machiavelli mainly on "Il Principe". This study shows that in making political policies, for the sake of government stability, moral values do not need to be considered except in a pragmatic context. The stability of the state is also influenced by the ability and luck of the leader in managing the government. This study shows that the practice of the Umayyad dynasty has a correlation with the main goal of Machiavelli's political theory, namely state stability.